The Correlation of Speed, Flexibility, and Agility on The Kick “T” of Tapak Suci Pencak Silat - Amrullah, Azhar Hasyim; Priyanto, Priyanto; Sugiarto, Sugiarto (Universitas Negeri Semarang, 2023)
Abstract. The purpose of this study was to determine the contribution of speed and flexibility to the agility of the “T” kick in male pencak silat athletes at Tapak Suci College, SMP Negeri 1 Matesih. The independent variables were speed (X1) and flexibility (X2), with the dependent variable being the “T” kick agility (Y) in pencak silat. The sample consisted of 31 athletes. The analysis was conducted using regression analysis. The results indicated that the significance values for speed and flexibility, both individually and combined, were significant. Therefore, the hypothesis that there is a contribution of speed and flexibility to the agility of the “T” kick in Tapak Suci pencak silat athletes at SMP Negeri 1 Matesih was accepted.Abstract in Indonesia. Tujuan dari penelitian ini adalah untuk mengetahui kontribusi kecepatan dan kelenturan terhadap kelincahan tendangan “T” pada atlet pencak silat laki-laki di Perguruan Tapak Suci, SMP Negeri 1 Matesih. Variabel bebas adalah kecepatan (X1) dan kelenturan (X2), dengan variabel terikat adalah kelincahan tendangan “T” (Y) dalam olahraga pencak silat. Sampel terdiri dari 31 atlet. Analisis dilakukan dengan menggunakan analisis regresi. Hasil penelitian menunjukkan bahwa nilai signifikansi untuk kecepatan dan kelenturan, baik secara individu maupun bersama-sama, signifikan. Oleh karena itu, hipotesis bahwa ada kontribusi kecepatan dan kelenturan terhadap kelincahan tendangan “T” pada atlet pencak silat Tapak Suci di SMP Negeri 1 Matesih diterima.